2012
DOI: 10.1177/0020872811433136
|View full text |Cite
|
Sign up to set email alerts
|

Who should play a major role in responding to intimate partner violence? A comparison of Chinese and American college students’ preferences

Abstract: Using survey data collected from 639 students in a Chinese university and an American university, this study assesses students' preferences for private, parochial, and public responses to intimate partner violence (IPV). The results show that Chinese students are in favor of a parochial approach, whereas American students prefer a criminal justice intervention to IPV. Preferences for different responses to IPV are predicted by locality, respondents' attitudes toward gender roles, tolerance for violence, and aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 28 publications
(25 reference statements)
3
28
0
Order By: Relevance
“…Furthermore, Chinese attitudes toward appropriate responses to IPV differ from those in Western countries. Chinese students are less likely to support a law enforcement approach to IPV than American students (Li et al, 2013; Wu et al, 2013). Chinese students were also more supportive of a traditional police response (nonintervening, belief that intervention is ineffective) to IPV and less supportive of a proactive police response (use of arrest, sympathetic to victim; see Sun, Li, & Wu, 2011; Sun, Su, & Wu, 2011).…”
Section: Ipv In the United States And Chinamentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, Chinese attitudes toward appropriate responses to IPV differ from those in Western countries. Chinese students are less likely to support a law enforcement approach to IPV than American students (Li et al, 2013; Wu et al, 2013). Chinese students were also more supportive of a traditional police response (nonintervening, belief that intervention is ineffective) to IPV and less supportive of a proactive police response (use of arrest, sympathetic to victim; see Sun, Li, & Wu, 2011; Sun, Su, & Wu, 2011).…”
Section: Ipv In the United States And Chinamentioning
confidence: 97%
“…Although some emerging research suggests that tolerance for IPV varies tremendously across cultural contexts (Allen & Devitt, 2012; García-Moreno et al, 2005; Hester, 2005; Nguyen et al, 2013; Speizer, 2010), little is known about the causal mechanisms of tolerant attitudes toward IPV in any particular culture. Given that tolerance for IPV and IPV perpetration and victimization are highly correlated (Archer & Graham-Kevan, 2003), and tolerance for IPV influences victims’ willingness to seek professional help (Li, Wu, & Sun, 2013), social service (Wu et al, 2013), and legal intervention (Giordano, Johnson, Manning, Longmore, & Minter, 2015; Sun et al, 2012), more research to identify the cultural-specific correlates of tolerance for IPV is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding similarities and differences in attribution of blame for partner violence and attitudes toward partner violence across cultures has implications for international transfer of effective measures and policies for combating relationship violence. For example, in comparing responses of Chinese and American university students, Li, Wu, and Sun (2013) found that Chinese students endorsed a "parochial" approach to addressing partner violence, in contrast to endorsement of a "criminal justice system" approach by students in the United States. By drawing attention to pervasive cross-cultural differences, the current findings enhance understanding of these differences in perceived causes of partner violence across cultures.…”
Section: Implications For Policy Practice Education and Researchmentioning
confidence: 99%
“…Public attitudes toward wife beating, however, vary considerably across different cultures and nations (Li, Wu, & Sun, 2013;Nayak, Byrne, Martin, & Abraham, 2003). The existing empirical literature on attitudes about wife beating in both Arab (e.g.…”
Section: Introductionmentioning
confidence: 99%